It’s dark under the lamp? The moderating role of executives’ accounting competence on relationship between goodwill impairment signal and goodwill impairment - Qiandan Deng (PLoS ONE, 2025)
This study examines the influence of executives’ accounting competence on relationship between goodwill impairment signal and goodwill impairment, considering the perspective of performance compensation commitment. The research employs an empirical research method and utilizes a sample of A-share listed companies in China that have signed performance compensation commitment agreements from 2007 to 2022. I found that the executives’ accounting competence weakens the relationship between goodwill impairment signal and goodwill impairment. The stronger the executives’ accounting competence is, the weaker the goodwill impairment signal is, that is, the probability of the goodwill impairment is lower and the scale of goodwill impairment is smaller. Further research shows that the negative effect of executives’ accounting competence is more significant when the performance compensation commitment of the target assets is between 80% and 100%. Through heterogeneity analysis, it is found that the negative effect of executives’ accounting competence will be suppressed when the sample is in the period of equity incentive or the auditor audits the key issues of goodwill impairment. The research in this paper not only enriches the relevant literature on the characteristics of executives, but also discusses the subsequent measurement of goodwill, which is also conducive to promoting the formulation of accounting standards and assisting the supervision of capital markets, and has important theoretical and practical significance.